1998
DOI: 10.1111/j.1572-0241.1998.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Treatment Serum Levels of Cytokines IL-1β, IL-6, and IL-1 Receptor Antagonist in Celiac Disease. Are They Related to the Associated Osteopenia?

Abstract: Our data demonstrate that the inflammatory process observed in active celiac disease is associated with high serum levels of IL-1beta and IL-6 and normal levels of IL-1-RA. Treatment significantly reduces both proinflammatory cytokines and significantly increases the antiinflammatory one. We also suggest that these cytokines might have a role in the osteopenia associated with celiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 20 publications
3
43
1
2
Order By: Relevance
“…In fact, mean serum levels of inflammatory cytokines that contribute to ACD, including interleukin-1β, interleukin-6, tumor necrosis factor-α, and interferon-γ, are increased in active celiac disease. [24][25][26][27] Our results hint at a defective production of endogenous erythropoietin, in addition to changes in iron homeostasis, as a pathogenetic mechanism of ACD. A defective production of erythropoietin for the degree of anemia has been reported in some studies on ACD, [28][29][30] although adequate erythropoietin levels were observed in ACD subjects with systemic juvenile chronic arthritis.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, mean serum levels of inflammatory cytokines that contribute to ACD, including interleukin-1β, interleukin-6, tumor necrosis factor-α, and interferon-γ, are increased in active celiac disease. [24][25][26][27] Our results hint at a defective production of endogenous erythropoietin, in addition to changes in iron homeostasis, as a pathogenetic mechanism of ACD. A defective production of erythropoietin for the degree of anemia has been reported in some studies on ACD, [28][29][30] although adequate erythropoietin levels were observed in ACD subjects with systemic juvenile chronic arthritis.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the levels of other pro-inflammatory cytokines such as IFN-γ, IL-1β and IL-6 have been increased in active coeliac patients in several studies (Fornari et al 1998;Kontakou et al 1994;Manavalan et al 2010;Nilsen et al 1998), but no significant increase was found in our CD Mab-treated mice compared to controls. This difference in the cytokine profile between coeliac patients and CD Mab-injected mice is not surprising, since the mice we used in the study were immunecompromised T-cell deficient mice and thus unable to mount the cytokine response characteristic of T-cellmediated adaptive immune activation.…”
Section: Discussionmentioning
confidence: 54%
“…These events include hypersecretion of parathyroid hormone (PTH), enhanced 1,25(OH) 2 -vitamin D, and diminished 25-OHvitamin D. The level of 1-α-hydroxylase enzyme is enhanced because the defective enterocytes cannot respond to 1,25(OH) 2 -vitamin D and eventually result in increased levels of PTH. In a conducted study by Fornari et al, 27 high levels of IL-1β, IL-6, and IL-1 receptor antagonists were found in untreated patients with celiac disease (n = 16, aged 18-75 years). Although strict diet adherence is important in children with celiac disease, early diagnosis and implementation of a gluten-free diet also play vital roles by ensuring increased activity of bone metabolism and obtaining peak bone mass.…”
Section: Effect Of a Gluten-free Diet On Body Composition Of Childrenmentioning
confidence: 93%